ANALISA POSTUR KERJA OPERATOR BAGIAN FINISHING MENGGUNAKAN METODE OVAKO WORK ANALYSIS SYSTEM (OWAS) DI CV. SARANA TEKNIK - Hidayat, Dian Friana; Miftahudin, Miftahudin (Journal Industrial Manufacturing, 2020)
The purpose of study is analysis the work posture of the finishing section on the CV. Sarana Teknik, in order to reduce musculoskeletal disorders using the Nordic Body Map, and the Ovako Work Analysis System (OWAS). CV. Sarana Teknik is an industry engaged in processing plastic pellets into various products on demand. These products are medicine caps and toys that are relatively small in size. The study was conducted in the finishing section with 6 operators. Based on the Nordic Body Map questionnaire, 49% of workers or 3 of 6 workers stated that they were somewhat sick to the point where they were examined at 28 points of the body. Then the work attitude analysis that defines the movement of body parts of the back, arms, legs and weight lifted using the Ovako Work Analysis System (OWAS). The results of this study are the body part is very painful, which is dominantly felt by all operators, is back by 100%. The observed work posture is the taking and tidying posture, the result of the analysis is the taking work posture is category 2 which is a dangerous attitude on the musculoskeletal system which results in a significant tension effect so that the posture needs improvement. As for the tidying work posture, category 1 is an attitude that has no problems so this attitude does not need to be improved.